Changes in the neurological status from 30 to 90 days post-cardiac arrest by age: A nationwide retrospective observational study - Hiromi Miyoshi; Mitsuaki Nishikimi; Kazuya Kikutani; Shinichiro Ohshimo; Nobuaki Shime (Resuscitation Plus)
Introduction: Few studies have investigated the changes in the neurological status after 30 days post-arrest in out-of-hospital cardiac arrest (OHCA) patients according to the patient age. The aim of this study was to investigate the differences in the mid-term (from 30 days to 90 days) neurological changes after CA according to the age group. Methods: We retrospectively analysed the data of all OHCA patients aged ≥1 year who showed return of spontaneous circulation and survived until 30 days after CA. We compared the proportions of patients who showed neurological deterioration from 30 to 90 days post-CA by age group (1–17, 18–39, 40–64, 65–79, ≥80 years). The neurological outcome was assessed by the Cerebral Performance Category (CPC) or Pediatric Cerebral Performance Category (PCPC) scale. Results: Of the 68,110 registered patients, we analysed the data of a total of 2,663 patients. The neurological deterioration rate and improvement rate from 30 to 90 days after CA in each age group were as follows: 1–17 years: 11.6% (8/69)/7.2% (5/69); 18–39 years: 8.3% (15/181)/6.1% (11/181); 40–64 years: 7.3% (72/982)/7.0% (69/982); 65–79 years: 13.5% (130/965)/8.1% (78/965); and ≥ 80 years: 24.2% (113/466)/4.9% (23/466). Multivariable logistic regression analysis showed a higher likelihood of mid-term neurological deterioration in patients aged ≥ 80 years than in those aged 1–17 years. Conclusions: Most OHCA patients, irrespective of age, showed no change of the neurological status from 30 to 90 days after OHCA. However, a relatively large percentage of patients aged ≥80 years old showed significant neurological deterioration after 30 days post-OHCA.